Taxonomic classification of mycobacteria of the mycobacterium chelonae-mycobacterium abscessus complex without conclusive species identification - Nogueira, Christiane Lourenço [UNIFESP] (2016)
The methodologies used to delineate bacterial species are changing with the development of new technologies. The Mycobacterium chelonae-Mycobacterium abscessus complex is composed of closely related rapidly growing mycobacteria that are ubiquitous in the environment and sometimes responsible for a wide spectrum of opportunistic infections in humans, especially pulmonary infections and localized skin and soft tissue infections. This complex has expanded over the years to include, besides the classical species M. chelonae and M. abscessus, also M. immunogenum, M. salmoniphilum, and two subspecies M. abscessus subsp. abscessus and M. abscessus subsp. bolletii. Despite all technological advances, the taxonomic relations of members of M. chelonae-M. abscessus complex still generate several doubts, due to important similarities in their phenotypic and genotypic characteristics. Considering the importance of correct species identification for understanding the taxonomy of this group and for outbreak detection and therapeutic patient management, the present project aimed at investigating the taxonomic position of a set of M. chelonae-M. abcessus complex isolates without conclusive species identification and a set of isolates of the CHII INNO-LiPA® cluster. A polyphasic approach, including phenotypic analyses traditionally used for identification of mycobacteria, drug susceptibility testing, the commercial test Genotype® Mycobacterium CM and AS, PCR Restriction Enzyme Analysis of the hsp65 gene and 16S-23S internal transcribed spacer (ITS), DNA sequencing of the 16S rRNA, hsp65 and rpoB genes and the 16S-23S ITS, DNA-DNA hybridization (DDH), Whole Genome Sequencing (WGS) and genome comparisons were carried out. The previously reported high variability of the CHII INNO-LiPA® cluster was confirmed. Two species were validly named as new members of M. chelonae-M. abscessus complex, M. franklinii and M. saopaulense, and three additional genomospecies were identified. Moreover, genomic analyses confirmed that the type strains of the M. chelonae-M. abscessus complex, including the two recently described species (M. franklinii and M. saopaulense), belong to different species, confirming the current taxonomic classification of this complex in the era of genomic taxonomy. This study illustrates the use of WGS to determine the taxonomic status of isolates which conventional tests fail to identify. Furthermore it emphasizes that 143 mycobacteria identification should not be performed based only in a single methodology. This study will be useful for future investigations of infections and outbreaks caused by members of M. chelonae-M. abscessus complex.